2007
DOI: 10.1007/s10558-007-9029-5
|View full text |Cite
|
Sign up to set email alerts
|

Chest Compression Force of Trained and Untrained CPR Rescuers

Abstract: The objective of this study was to measure the force exerted by 83 trained CPR rescuers and 104 untrained adult laypersons (college students and staff). A bathroom scale was used to measure the force exerted by these subjects with their hands on the bathroom scale in the CPR position. The weight range for both groups was the same. Of the trained rescuers, 60% pressed with more than 125 lbs, whereas only 37% of the laypersons pressed with more than 125 lbs. In view of the American Heart Association (AHA) guidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Other studies documented a relationship between rate and depth 1 , 25 27 , force and depth 28 , 29 , and weight and force 28 . It is estimated that chest depression of 5 cm requires about 56.7 kg of body weight 28 . Geddes and colleagues found that only 9% of untrained laypersons and about 1% of trained rescuers performed CC with a force that exceeds their body weight.…”
Section: Discussionmentioning
confidence: 96%
“…Other studies documented a relationship between rate and depth 1 , 25 27 , force and depth 28 , 29 , and weight and force 28 . It is estimated that chest depression of 5 cm requires about 56.7 kg of body weight 28 . Geddes and colleagues found that only 9% of untrained laypersons and about 1% of trained rescuers performed CC with a force that exceeds their body weight.…”
Section: Discussionmentioning
confidence: 96%
“…No visual or acoustic feedback was permitted during CC. Each CC method was performed on a load cell (CAS Korea, Seoul, South Korea) to obtain and compare the compression force [15].…”
Section: Study Design and Protocolmentioning
confidence: 99%
“…This amount of force frequently causes rib fractures in human patients and is extremely tiring for the individuals performing CPR. [33][34][35] Zeh 36 found that the required mechanical energy for fist pacing in people is approximated by allowing the ulnar side of the fist to fall from a height of 20-30 cm above the chest. Zoll 25 …”
Section: Performing Transcutaneous Cardiac Pacingmentioning
confidence: 99%